2005
DOI: 10.1258/0004563053857806
|View full text |Cite
|
Sign up to set email alerts
|

An innovative Australian point-of-care model for urine albumin: creatinine ratio testing that supports diabetes management in indigenous medical services and has international application

Abstract: This unique POC model for supporting diabetes management is the first of its type to be developed for indigenous communities and has considerable potential to be adopted worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Large-scale national models such as the QAAMS PoCT program for diabetes management in Aboriginal and Torres Strait Islander medical services has provided a sound evidence base for the analytical, clinical and cultural effectiveness of PoCT in this most challenging of primary health care environments. 48,68,71 While local PoCT models have been developed for use in the Australian rural general practice environment 47 , the evidence base for the usefulness of PoCT in general practice both within Australia and globally has thus far been limited. 3,13 The objectives of this component of the PoCT Trial in General Practice were to develop, deliver and manage both:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Large-scale national models such as the QAAMS PoCT program for diabetes management in Aboriginal and Torres Strait Islander medical services has provided a sound evidence base for the analytical, clinical and cultural effectiveness of PoCT in this most challenging of primary health care environments. 48,68,71 While local PoCT models have been developed for use in the Australian rural general practice environment 47 , the evidence base for the usefulness of PoCT in general practice both within Australia and globally has thus far been limited. 3,13 The objectives of this component of the PoCT Trial in General Practice were to develop, deliver and manage both:…”
Section: Discussionmentioning
confidence: 99%
“…44 Four of the RCTs investigated PoCT with another intervention. 8,18,21,34,58,59 The geographical setting included the United Kingdom (n=13) 8,16,18,21,33,[60][61][62][63][64][65][66][67] , Australia (n=7) 17,23,47,[68][69][70][71] , USA (n=5) 44,58,[72][73][74] , Belgium (n=2) 34,59 , Sweden (n=1) 75 and Ireland (n=1). 76 A description of the 29 studies included in the review is reported in Table 13 and Table 14.…”
Section: Excluded Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, there is evidence to suggest that Aboriginal and Torres Strait Islander Health Workers (ATSIHW), otherwise known as Indigenous Health Workers (IHW), may help to improve attendance at appointments and acceptance of treatment and assessment recommendations [9], reduce discharge against medical advice, increase patient contact time, enhance patient referral linkages, and improve patient follow up practices [13]. Preliminary evidence also shows potential for IHWs to improve diabetes screening [15,16] and care management processes [17,18], as well as palliative care [19] and maternal and infant care [20].…”
Section: Introductionmentioning
confidence: 99%